Economics and the common law : - Deserpa, Allan C. (Thomson, 2005)
Designed more to complement an existing text on the subject of Law & Economics, this casebook has more complete cases than the leading texts. Brief sections follow the cases in order to highlight the key points of economic analysis. The text fulfills the need for more complete case material, and important case material, that is sometimes glossed over in texts. At the same time, the analyses provide summaries of the key economic elements to the cases.